MODEL PENULARAN PENYAKIT DEMAM BERDARAH DENGUE (DBD) DALAM SYSTEM DYNAMIK BERDIMENSI DUA - Posma Lumbanraja (Universitas Methodist Indonesia, 2021)
Here we examine the dynamic model of the spread of Dengue Hemorrhagic Fever (DHF) assuming a constant number of host and vector populations. In this paper, the model is reduced from a three-dimensional system to a two-dimensional system so that the dynamic behavior can be analyzed in the R2 plane. In the two-dimensional model, if the threshold parameter R > 1, the endemic state becomes globally asymptotically stable. During the analysis of its dynamic behavior, a trapping region is found which contains a heteroclinic orbit connecting the slowing point, namely the origin and the endemic point. By using heteroclinic orbits, it can be estimated the time period required from a state to reach a certain state.